Pengaruh Media Google Earth Terhadap Materi Tata Letak Dan Denah Pada Peserta Didik Kelas IV SD Negeri 02 Papahan Tasikmadu Tahun Pelajaran 2022/2023 - Tiya Ayu Isnaini Fitrotiha; Oktiana Handini; Ani Restuningsih (Departement of Mathematics Education, 2023)
This research aims to investigate whether or not Google Earth has an influence on Layout and Floor Plan Material for Grade IV Students at SD Negeri 02 Papahan Tasikmadu in the 2022/2023 Academic Year. In addition, it is also to find out whether there are obstacles and benefits of Google Earth Media for Layout and Floor Plan Material for Class IV Students at SD Negeri 02 Papahan Tasikmadu for the 2022/2023 Academic Year. This research has a population of 32 students from Class IV A, namely SD Negeri 02 Papahan Tasikmadu for the 2022/2023 academic year with a saturated sampling technique. Furthermore, the data collection techniques used are observation and learning achievement tests. Observation is used to observe students' initial conditions before being given treatment and learning outcomes tests in the form of multiple choice questions after being given treatment. The analysis technique is carried out in 2 ways, namely: from the prerequisite test and the t-test. The prerequisite test consists of the normality test and homogeneity test. Meanwhile, the t-test uses the Paired Sample T-test. Analysis of the use of the t-test formula in the form of a Paired Sample T-Test yields, if a significant value is 0.001 > 0.05, it can be said that H0 is rejected and Ha is accepted. In addition, the value of tcount = 16.030 can be compared with the value of ttable with the value of dk = (N-1) then (32-1) = 29 at a level at a significance level of 5% will have a ttable value of 2.042. When compared tcount and ttable then 16.030 > 2.042. Alternative hypothesis (Ha), is accepted if tcount > ttable. The next hypothesis could be